Does corporate sustainable development still promote corporate financial performance during global crises? Empirical Study from China - Ruba Hamed; Wasim Al-Shattarat; Faisal Mahmood; Basiem Al-Shattarat; Ahmed Hassanein (Cogent Business & Management, 2023)
The purpose of this study is to find out how the positive influence of corporate sustainable development on corporate financial performance alters during the two recent crises i.e. the global recession (2008-10) and COVID-19 (2019-20). The fixed effect modeling of panel data is applied in the main analysis of Chinese manufacturing companies ranging from 2008 to 2020. The results of the study disclose that there is an overall positive influence of corporate sustainable development on corporate financial performance. However, this influence becomes stronger during both crises i.e. the global recession (2008-10) and COVID-19 (2019-20). Moreover, this positive influence is even stronger during covid −19 recession as compared to this influence during the global recession (2008-10).
Keywords: M14; M41; 650; Covid-19 (2019-20); financial performance; global recession (2008-10); Sustainable development